Cardiopulmonary resuscitation in parturients: Assessment of anesthesiologists’ knowledge (Annals of Medical Research, 2021)
Aim: Cardiac arrest in pregnancy is one of the most challenging clinical scenarios. Correct intervention plays a crucial role in increasing the chance of survival of both the baby and the mother. In this study we aimed to evaluate knowledge about resuscitation of parturients among anesthesiologists.Materials and Methods: A total of 356 anesthesiologists (162 anesthesiology residents, 146 anesthesiology specialists and 48 faculty member) were included in the study. The subjects of the study population were chosen among the anesthesiologists with various levels of experience who attended to national anesthesia meetings that were held from January 2015 to December 2015 in Turkey. The assessment was based on a questionnaire containing 10 questions and questions were designed to draw out knowledge deficiencies in critical areas of cardiopulmonary resuscitation in parturients. Results: There was a significant correlation between the age and the total score (r=0.198 / p=0.000). Concerning the effect of the occupational title, we found that the total score of the specialist group was significantly higher than that of the resident group (p=0.001). There was no correlation between the total score and having a CPR experience in parturients. Conclusion: The results of our study indicate that there is a lack of knowledge about the CPR in parturients in Turkey. Therefore education programs about the management of cardiac arrest and CPR in parturients should be planned and repeated on a regular basis.
Keywords: Anesthesiologists’ knowledge; Cardiopulmonary resuscitation; parturients